1996
DOI: 10.1111/j.1553-2712.1996.tb03347.x
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Screens Stable Patients at Risk for Penetrating Cardiac Injury

Abstract: Objective: To determine the accuracy of CT of the chest in diagnosing the presence of cardiac injury in stable pitients with penetrating chest injuries. Methods: A retrospective chart review of a convenience sample of stable patients with penetrating thoracic wounds evaluated for hemopericardium using chest CT at an urban level I trauma center. Results: 60 stable patients with penetrating wounds in proximity to the heart underwent CT. Three patients had radiographic evidence of pericardial fluid, and 1 had an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 11 publications
0
19
0
1
Order By: Relevance
“…Nagy and colleagues [42] substituted conventional chest CT when echocardiography was not available to diagnose hemopericardium. The study included 45 patients who had precordial stab wounds and 15 patients who had transmediastinal gunshot wounds.…”
Section: Cardiac and Pericardial Injuriesmentioning
confidence: 99%
“…Nagy and colleagues [42] substituted conventional chest CT when echocardiography was not available to diagnose hemopericardium. The study included 45 patients who had precordial stab wounds and 15 patients who had transmediastinal gunshot wounds.…”
Section: Cardiac and Pericardial Injuriesmentioning
confidence: 99%
“…That appearance allows the fracture of the sternum and a stab wound of the heart. Despite the long time that foreign body remained in the sternum (for several hours in this case) we do not have sternum osteomyelitis or endocarditis, as described in some cases [5, 6]. …”
Section: Discussionmentioning
confidence: 62%
“…Usually cardiac ultrasound is enough for diagnosis [4], but in patient with stable blood pressure such as this case, CT scan gives more information about cardiac wound and presence of pericardial blood effusion [5]. …”
Section: Discussionmentioning
confidence: 99%
“…With the accessibility of CT scanners, more recent studies have shown that CT scan can detect significant injuries with a sensitivity of 100% and specificity of 97% (14). However, only patients who are indisputably hemodynamically stable enough to leave the trauma bay to undergo a scan should be evaluated in this fashion.…”
Section: Discussionmentioning
confidence: 99%